The Future Is Now: Legal Planning for Elders - Eastman, Jennifer (Maine Policy Review, 2015)
Legal planning for elders focuses on protecting retirement income and finding ways to pay for long-term health care. Jennifer Eastman discusses estate and tax planning and planning for retirement income, Social Security issues, and asset preservation. She notes that protecting elder adults requires planning and advocating for (or against) policy changes that could adversely affect elders.
Keywords: aging; legal planning; tax planning; retirement income; Social Security; asset preservation